Biochar affects growth and shoot nitrogen in four crops for two soils. Issue 1 (16th August 2020) - Olszyk, David; Shiroyama, Tamotsu; Novak, Jeffrey; Cantrell, Keri; Sigua, Gilbert; Watts, Donald; Johnson, Mark G.
Abstract: To address the need for information on biochar effects on crop growth and nitrogen (N), a greenhouse study was conducted with carrot, lettuce, soybean, and sweet corn using sandy loam (Coxville series) and loamy sand (Norfolk series) soils and a variety of biochars. Biochar was produced from pine chips (PC), poultry litter (PL), swine solids (SS), switchgrass (SG), and two blends of PC plus PL (50/50% [55] and 80/20% [82], wt/wt), with each feedstock pyrolyzed at 350, 500, or 700 ˚C. The results confirmed that biochar can increase crop growth; however, the responses varied with crop, soil, and feedstock and to a lesser extent with pyrolysis temperature. In general, lettuce had large increases in shoot and root dry weights vs. no‐biochar controls with many biochars, primarily the SS and 55 blend and to a lesser extent with 82 followed by PL, and then PC and SG, especially when grown in the Coxville soil. Biochar had more limited effects on carrot, sweet corn, and soybean weights. Some biochars decreased crop growth (e.g., PL at 700 ˚C) for soybean shoot and pod dry weights with the Norfolk soil. Shoot N concentrations decreased with SS, 55, and 82 for carrot, lettuce, and sweet corn with the Norfolk soil but tended to increase for soybean. Shoot N uptake increased or decreased depending on biochar feedstock and temperature, crop, and soil. These results confirm that biochar can increase crop growth and affect shoot N, which is essential for crop growth.